first of all thanks for the answer but...
The answer (i have a only the final answer) is λ^-1(1- e^-λ) and you said that so isn't the sum above shoudnt be (1- e^-λ) instead of 1???d
first of all thanks for the answer but...
The answer (i have a only the final answer) is λ^-1(1- e^-λ) and you said that so isn't the sum above shoudnt be (1- e^-λ) instead of 1???d
first of all thanks for the answer but...
The answer (i have a only the final answer) is λ^-1(1- e^-λ) and you said that so isn't the sum above shoudnt be (1- e^-λ) instead of 1???d